Analisa Pengaruh Rasio Keuangan Terhadap ROA Pada PT. Bank mandiri, Persero (Tbk) - Murtiningrum, Widiastuti (Sekolah Tinggi Manajemen IMMI Jakarta, 2023)
With a consistent business strategy and mature digitalization optimization, Bank Mandiri managed to record good financial performance, as seen from the profit in the 1st quarter of 2023, which was the result of a performance focused on the business ecosystem approach both from financing and funding. The credit increase was due to the improving solid economic fundamentals, Bank Mandiri seeks to contribute to the Indonesian economy. The condition of Indonesian banking after the Covid pandemic began to improve, as seen from the increase in the capital adequacy ratio (CAR), the ratio of non-performing loans (NPL), an increase in net interest income (NIM), a decrease in the ratio of operating expenses to operating income (BOPO), with high capital owned there is an increase in the fulfillment of loan requests (LDR) with a low ratio level. This research was conducted by analyzing, testing and concluding the effect of CAR, NPL, NIM, BOPO and LDR on ROA at Bank Mandiri for the 2017-2023 period using secondary data through information on Bank Mandiri's financial reports. Quantitative analysis technique with multiple linear regression and classical assumption test using SPSS version 25. The results show BOPO, NIM and LDR partially have a positive and significant effect, while CAR and NPL do not have a significant effect on ROA Simultaneously CAR, BOPO, NPL, NIM and LDR affect the increase or decrease in ROA. From the independent variable to the dependent variable it has a predictive ability of 98.3% and 1.7% is influenced by other variables outside the research.